1985
DOI: 10.1002/j.1460-2075.1985.tb03926.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated alternate modes of expression of the Gpdh locus of Drosophila.

Abstract: Immunoblot analyses have been performed on extracts prepared from Drosophila melanogaster. Those analyses have revealed two subunit forms of enzyme glycerol 3‐phosphate dehydrogenase (GPDH) in larval tissues and in adult abdominal tissues. Thoracic tissue, which accounts for the bulk of the adult GPDH, has only one subunit form, the smaller. The two subunit forms differ by approximately 2400 daltons. In agreement with previous genetic and biochemical data indicating that this enzyme is encoded by a single stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Probes for the transcript of the ribosomal protein rp49 were used as a control. (B) Developmental Westem blot; Extracts were prepared from flies at the indicated number of days after emergence, electrophoresed on 12.5% SDS-polyacrylamide gels, electroblotted, and reacted with anti-GPDH serum as described previously (Skuse and Sullivan, 1985). were stained for GPDH, and we observed that the great majority, if not all, of GPDH-1 in flight muscles is found localized along the sarcomere of the myofibrils in an ordered pattern of alternating strongly fluorescent and somewhat more weakly fluorescent zones ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Probes for the transcript of the ribosomal protein rp49 were used as a control. (B) Developmental Westem blot; Extracts were prepared from flies at the indicated number of days after emergence, electrophoresed on 12.5% SDS-polyacrylamide gels, electroblotted, and reacted with anti-GPDH serum as described previously (Skuse and Sullivan, 1985). were stained for GPDH, and we observed that the great majority, if not all, of GPDH-1 in flight muscles is found localized along the sarcomere of the myofibrils in an ordered pattern of alternating strongly fluorescent and somewhat more weakly fluorescent zones ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…GPDH-3 is normally found in nonmuscle cells, but its localization in nonmuscle cells has not yet been characterized. However, because GPDH-3 is known to participate with glycerol-3-phosphate oxidase, a known mitochondrial enzyme, in accomplishing the glycerolphosphate shuttle (MacIntyre and Davis, 1987) (Skuse and Sullivan, 1985). though variable, is within the range that might be expected for a set of lines carrying independent transposons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations